In vivo precision of digital static interocclusal registration for full arch and quadrant arch scans: a randomized controlled clinical trial - Noha Morsy; Mohammed El Kateb (BMC Oral Health, 2022)
Abstract Background Clinical studies comparing the accuracy of digital and conventional records for static interocclusal registration are lacking. Therefore, the purpose of this clinical study was to assess the precision of digital interocclusal registration compared to conventional registration for full arch and quadrant arch conditions. Methods Nine individuals with complete natural dentition were enrolled in this study. Each participant received digital scans, conventional impressions, and static interocclusal records according to the following groups: group DF, full arch digital scans and bilateral buccal scans with Medit i700 intraoral scanner (IOS); group DQ, quadrant arch digital scans and unilateral buccal scans with Medit i700 IOS; group CF, full arch polyvinyl siloxane (PVS) impressions and PVS interocclusal records; group CQ, quadrant arch PVS impressions and PVS interocclusal records. For group CF and group CQ, the impressions were poured, mounted with the silicone bites, scanned with a laboratory scanner, and articulated virtually with buccal scans with the laboratory scanner. In each group, each participant received three interocclusal records to repeat the virtual articulation three times and the articulated models were saved as STL files. The STL files were imported into a 3D-processing software to calculate the discrepancies between repeated measures using best-fit-alignment method. The significance between the study groups was calculated with two-tailed paired t-test at P < 0.05. Results For full arch, group DF showed significantly better precision with a mean value of 31 ± 19 µm compared to 204 ± 81 µm for group CF (P = 0.0003). Similarly, for quadrant arch, group DQ showed significantly better precision with a mean value of 18 ± 6 µm compared to 255 ± 136 µm for group CQ (P = 0.0009). No significant difference in precision was found between quadrant arch and full arch when the digital or the conventional method was used. Conclusions The digital approach had significantly better precision for static interocclusal registration compared to the conventional method in both full and quadrant arch situations. Trial Registry This clinical trial was registered on 06/07/2022 in the Pan African Clinical Trial Registry database, the number for the registry is PACTR202207648490275.